Análisis desde una perspectiva tributaria de la implementación de negocios de crowdfunding o financiamiento participativo basados en el modelo de préstamo - Mego Chavez, Wilfredo (2021)
For the implementation of new businesses and projects with Information and Communication Technologies —ICT—, it is necessary to have an adequate and permanent tax support, since the non-compliance of the tax aspects of an operation could result in cost overruns for entrepreneurs by generating very high tax burdens or even the loss of benefits. In this context, the purpose of this article is to analyze from a tax perspective the implementation of crowdfunding or participatory financing businesses under the loan model; since it constitutes an emerging financing mechanism, in which the founders of new businesses and projectshave found an attractive alternative to conventional models —e.g. bank loans—.